Advanced Research on Non-small Cell Lung Cancer with De Novo T790M Mutation - Xin WANG; Diansheng ZHONG (Chinese Journal of Lung Cancer, 2019)
With the development of sequencing technology, the detection rate of de novo T790M mutation is increasing. The emergence of the third generation of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) provide treatment opportunities. Secondary T790M mutation is often emphasized in clinic, but de novo T790M mutation is neglected. This review found that the incidence of de novo T790M mutation fluctuated greatly, which was mainly affected by sequencing techniques. The de novo T790M mutation is mainly low in mutation abundance, easy to combine with other gene changes, a poor predictor and prognostic factor and the efficacy of the first and second generation EGFR-TKIs is limited. The therapeutic value of osimertinib needs to be studied.